Efektivitas Penyaluran Bantuan Sosial Pemerintah untuk Mengatasi Dampak Covid-19 di Indonesia - Noni Noerkaisar (Direktorat Sistem Perbendaharaan, 2021)
Abstract The spread of the Covid-19 pandemic resulted in a domino effect for all the sectors starting from health issues to social issues, economic, and political. Facing this situation, the government has designed various Social Safety Network policies as an effort to protect susceptible and affected communities from the COVID-19 pandemic. The next problem that occurs is during social assistance which is disbursed by the government, such as the inaccurate targeting of social assistance recipients. Therefore, this study was conducted to analyze further the distribution effectiveness on social assistance provided by the government to overcome the impact because of Covid-19 pandemic in Indonesia. This study used a qualitative approach based on literature studies or research-oriented to the secondary information collected from various related sources. The results of this study showed that the social assistance distributed by the government is still not effective. It was because there were still inaccuracies in the social assistance recipients, unequal distribution of assistance, long distribution, misappropriation of funds, illegal levies, nominal amounts reduction, and resources received, errors inclusion and exclusion, to the social assistance politicization. Abstrak Penyebaran wabah Covid-19 mengakibatkan efek domino bagi semua sektor yang berawal dari persoalan kesehatan ke persoalan sosial, ekonomi, hingga politik. Menghadapi situasi tersebut pemerintah telah merancang berbagai kebijakan Jaringan Pengaman Sosial dalam upaya melindungi masyarakat rentan serta terdampak dari pandemi Covid-19. Permasalahan selanjutnya yang senantiasa timbul saat bantuan sosial digelontorkan oleh pemerintah yakni adanya ketidaktepatan sasaran penerima bantuan sosial. Oleh karenanya riset ini dilakukan untuk menganalisis lebih lanjut efektivitas penyaluran bantuan sosial yang diberikan pemerintah untuk mengatasi dampak penyebaran Covid-19 di Indonesia. Penelitian ini menggunakan kaidah kualitatif berdasarkan studi literatur, yaitu kaidah riset yang berorientasi pada pengumpulan informasi sekunder dari bermacam sumber terkait. Hasil penelitian diketahui bahwa bantuan sosial yang disalurkan oleh pemerintah hingga saat ini masih belum efektif. Hal tersebut dikarenakan masih terdapat ketidaktepatan sasaran penerimaan bantuan, ketidakmerataan penyaluran bantuan, pendistribusian yang lama, penyelewengan dana, pungutan liar, pengurangan jumlah nominal maupun sumber daya yang diterima, inclusion dan exclusion error, hingga politisasi bantuan sosial.